Bisphenol A and Bisphenol S release in milk under household conditions from baby bottles marketed in Italy. Issue 2 (1st February 2018) - Russo, Giacomo; Barbato, Francesco; Cardone, Eleonora; Fattore, Margherita; Albrizio, Stefania; Grumetto, Lucia
ABSTRACT: A simple and sensitive validated analytical method based on liquid chromatography coupled to tandem fluorescence (FD) and ultraviolet (UV) spectrophotometry was applied to monitor the presence of bisphenol A and bisphenol S in plastic baby bottles marketed in Italy. The limits of detection (LOD) were 3.75 ng mL −1 and 80.00 ng mL −1, and those of quantification (LOQ) were 12.51 ng mL −1 and 260.00 ng mL −1 for BPA (FD detection) and for BPS (UV detection), respectively. BPA was found in only four samples, two samples undergone to microwave heating and two samples undergone to bottle warmer heating either at 40°C or at 80°C. Although the quantities of leached BPA were well below the reference dose for daily intake established by the European Food Safety Authority (EFSA) (4.0 µg kg −1 bw/day), the release of BPA and BPS from these plastic materials should be carefully considered by the government authorities to increase people's awareness on this issue and to protect the most vulnerable population group.